2022
DOI: 10.1177/00037028221101634
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy Study of Skin Biopsies from Patients with Parkinson’s Disease: Trends in Alpha-Synuclein Aggregation from the Amide I Region

Abstract: Parkinson's disease (PD) is one of the most common neurological pathologies with a high prevalence worldwide. PD is characterized by Lewy bodies, whose major component is the aggregates of α-synuclein (αSyn) protein. Interestingly, recent works have demonstrated that skin biopsy studies are a promising diagnostic tool for evaluating α-synucleinopathies. In this sense, this work focuses on the detection of αSyn in skin biopsies employing Raman spectroscopy, using three different approaches: 1) the in vitro Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The deviations of the spectra from the average spectrum are small, which may indicate a more uniform structure of βA at all investigated points of the Ag SERS substrate. It is known that the amide I region is empowered for protein conformational change [ 30 , 31 ]. The Ag SERS substrate is the same in all experiments, ZnO-NPs or the ZnO-Ag combination likely has a stabilizing effect on a certain structure of the protein or the formation of a certain specific structure.…”
Section: Resultsmentioning
confidence: 99%
“…The deviations of the spectra from the average spectrum are small, which may indicate a more uniform structure of βA at all investigated points of the Ag SERS substrate. It is known that the amide I region is empowered for protein conformational change [ 30 , 31 ]. The Ag SERS substrate is the same in all experiments, ZnO-NPs or the ZnO-Ag combination likely has a stabilizing effect on a certain structure of the protein or the formation of a certain specific structure.…”
Section: Resultsmentioning
confidence: 99%
“…León-Bejarano and colleagues utilized SERS to analyze α-synuclein levels in skin biopsies from PD patients. 189 Their study revealed distinct alterations in the Raman bands of the protein, with shifts observed from 1655, 1664, and 1680 cm −1 to 1650, 1670, and 1687 cm −1 when comparing control subjects to those with PD. These spectral changes were attributed to protein aggregation, suggesting the potential of SERS in detecting aggregated α-synuclein in skin samples.…”
Section: Liquid Biopsy Investigation For Brain Disorders Through Spon...mentioning
confidence: 95%
“…188 We would like to note that researchers have utilized diseased cells or tissues in order to diagnose different NDs. 23,189 For instance, in HD, RS has previously been used to study fibroblast from patients. [190][191][192] Wang et al introduced graphene-assisted RS for rapid biomarker sensing of AD.…”
Section: Cerebrospinal Fluid (Csf)-based Investigationsmentioning
confidence: 99%
“…When comparing the control and PD groups, the Raman spectra changed from 1,655, 1,664, and 1,680 cm −1 to 1,650, 1,670, and 1,687 cm −1 , respectively, which are related to protein aggregation. Research has shown that SERS can detect α-synuclein aggregates in the skin and thus this could be used as a minimally invasive tool for detecting the disease (León-Bejarano et al, 2022). Sevgi et al (2021) conducted Raman spectral and microspectral analyses of the olfactory bulb from the brain of human BAC-SNCA transgenic rats and samples of colon muscular and mucosal tissue sections.…”
Section: Raman Spectroscopy In Pdmentioning
confidence: 99%